PATHOGENICITY AND ULTRASTRUCTURAL STUDIES OF THE MODE OF PENETRATION BY Phyllosticta plantaginis IN RIBWORT LEAVES - Beata Zimowska (Acta Scientiarum Polonorum: Hortorum Cultus, 2014)
Pathogenicity and ultrastructural investigation of the ribwort leaves inoculated with Phyllosticta plantaginis conidia was undertaken using scanning electron microscopy to examine the host-parasite relationship. Pathogenicity experiments demonstrated that all tested P. plantaginis isolates had infected leaves of ribwort. Of all inoculation methods, direct placement of colonized agar plugs on damaged epidermis and soaking leaves in conidial suspension were the most effective. The behavior of the conidia deposited on the leaves was investigated at different time intervals after inoculation: 7, 18, 25, 48 and 72 h. An appressorium appeared directly at the end of a short germ tube grown from conidia. Appressoria were formed over the cuticle in some distance from the stomata. Penetration through the stomata was observed.